PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATA PELAJARAN SISTEM BAHAN BAKAR MOTOR BENSIN SISWA KELAS XI TSM DI SMK BINA MANDIRI KLAMPOK BANJARNEGARA TAHUN AJARAN 2015/2016 - Arifin Prasetya; Subagyo Subagyo (Jurnal Taman Vokasi, 2016)
This study aimed to know (1) the use of audio visual to improve learning motivation and (2) learning achievement of motor fuel system among the eleventh grade students of vocational school Bina Mandiri Klampok Banjarnegara in academic year 2015/2016. The type of this study was a classroom action research. Data collection techniques used questionnaire to know learning motivation and test to know learning achievement of motor fuel system. The research instruments were questionnaire and test. Data analysis technique used qualitative analysis.  This study shows that (1) the use of audio visual could improve learning motivation among the eleventh grade students of vocational school Bina Mandiri Klampok Banjarnegara in academic year 2015/2016. The average percentage of learning motivation in cycle I was 70.03 in fair category at the interval between 65,85 <  ≤ 84,15. The average percentage of learning motivation in cycle II was 84.75 in fair category at the interval between 84,15 <  ≤ 102,45. The average percentage of learning motivation in cycle III was 100.34 in fair category at the interval between 65,85  <  ≤ 84,15.  (2) The use of audio visual could improve learning achievement of motor fuel system among the eleventh grade students of vocational school Bina Mandiri Klampok Banjarnegara in academic year 2015/2016. The average score of test in pre cycle was 61.29, cycle I was 71.39, cycle II was 76.59, and cycle III was 81.15.  Based on these results, it could be concluded that the use of audio visual could improve learning motivation and learning achievement of motor fuel system among the eleventh grade students of vocational school Bina Mandiri Klampok Banjarnegara in academic year 2015/2016